Theoretical studies on a rotating film reactor for hydrogen production from methane - Becker, Tobias; Agar, David W. (Technische Universität Dortmund, 2022)
A film of liquid metal can protect the reactor wall from carbon deposits during methane pyrolysis, discharge carbon from the reactor and prevent blocking. The film can be generated by rotation in a rotating film reactor. Parameters such as liquid volume flow, operating mode or the diameter of the reactor can have an influence on the reaction behavior. A design of experiments was used to investigate the rotating film reactor in more detail and to characterize the influence of various parameters.
Chemie - Ingenieur - Technik;94(5)
Keywords: Carbon deposition; Hydrogen; Methane pyrolysis; Reactor modeling; 660; Sequestrierung; Wasserstoff; Pyrolyse; Methan; Chemischer Reaktor; Wasserstofferzeugung